Synthesis of 5,6-O-cyclohexylidene-1-amino-3-azahexane and its Co(II), Ni(II), Cu(II) complexes - Özturk, ÖF; Sekerci, M; Özdemir, E (Pleiades Publishing Ltd, 2005)
5,6-O-Cyclohexylidene-1-amino-3-azahexane (L) is synthesized from 1-chloro-2,3-0-cyclohexylidenepropane, which is prepared by the reaction between epichlorohydrin and cyclohexanone. In this reaction, (BF3OEt2)-O-. is used as a catalyst. Complexes of Co(II), Ni(II) and Cu(II) acetates with this ligand are prepared. The structures of the ligand and its complexes are proposed based on elemental analysis, IR and UV-VIS spectroscopy, magnetic susceptibility, conductometry, and H-1 and C-13 NMR spectroscopy.
Keywords: Corrosion